2019
DOI: 10.1111/cup.13459
|View full text |Cite
|
Sign up to set email alerts
|

Muir‐Torre syndrome appropriate use criteria: Effect of patient age on appropriate use scores

Abstract: Background Muir‐Torre syndrome (MTS) is a rare inherited syndrome, with an increased risk of sebaceous and visceral malignancy. Prior reports suggest screening for mismatch repair (MMR) deficiency may be warranted in patients <50 years and when sebaceous neoplasms are located on a non‐head and neck location. Previously, appropriate use criteria (AUC) were developed for clinical scenarios in patients >60 years concerning the use of MMR protein immunohistochemistry (MMRP‐IHC). This analysis explores the appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…In this study of 11 patients, the median (range) age at time of SN biopsy was 60 (33-78) years. Based on appropriate use criteria for MTS screening by IHC in patients 60 years or younger, it is deemed usually appropriate (the strongest consensus agreement category) to screen patients with multiple SNs (>2) or those with 1 SN on an extrafacial site . Everett et al demonstrated that patients with MTS are more likely to present with multiple SNs and at a younger age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study of 11 patients, the median (range) age at time of SN biopsy was 60 (33-78) years. Based on appropriate use criteria for MTS screening by IHC in patients 60 years or younger, it is deemed usually appropriate (the strongest consensus agreement category) to screen patients with multiple SNs (>2) or those with 1 SN on an extrafacial site . Everett et al demonstrated that patients with MTS are more likely to present with multiple SNs and at a younger age.…”
Section: Discussionmentioning
confidence: 99%
“…Universal screening of SNs with mismatch repair protein (MMRP) immunohistochemistry (IHC) has previously been recommended by some physicians to detect potential probands but has been debated given the high costs and variable sensitivities of detecting MTS, ranging from 25% to 85% depending on the IHC panel used . Sensitivity may increase with targeted screening, such as when a patient (of any age) presents with multiple SNs . Because MTS is caused by germline genetic mutations, it is presumed that individual SNs should harbor the same mutation.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent breakthrough in this area are vaccines for immunoprevention of DNA mismatch repair deficient cancers, which show promising results in initial phases (25). There are approximatively 200 other cases reported in the literature describing this syndrome, thus emphasizing the particularity of this case (26)(27)(28)(29)(30)(31). Without strong evidence for specific treatment or prophylaxis options for these patients, active screening and managing tumours in the early stages seems the best available approach.…”
Section: Discussionmentioning
confidence: 99%
“…4 For patients older than 60 years who develop sebaceous neoplasms, and patients of at least 60 years of age who develop a sebaceous tumor on or below the neck, immunohistochemical staining for mismatch repair proteins is recommended. 5 For those with abnormal mismatch repair protein results, visceral screenings, such as a colonoscopy and mammogram, in addition to genetic counseling are advised. Our patient’s annual mammogram and colonoscopy showed no abnormalities.…”
Section: Discussionmentioning
confidence: 99%